Different social contexts of leisure-time physical activity: Does the association with depressive symptoms differ?. (March 2021) - Werneck, André O.; Schuch, Felipe B.; Fernandes, Rômulo A.; Stubbs, Brendon; Szwarcwald, Célia L.; Silva, Danilo R.
Abstract: Our aim was to analyze the association between different social contexts of physical activity (PA) and depressive symptoms. Data from the Brazilian National Health Survey (PNS) (n = 59, 722; ≥18 years) were used. The social context of leisure-time PA [classified according to the higher probability of being practiced in group (group PA) or individually (individual PA)] and total PA time were self-reported. Depressive symptoms were evaluated through the Patient Health Questionnaire-9. Chronological age, ethnicity, educational status, employment status, tobacco smoking, alcohol ingestion, and soft drink consumption were co-variables. Logistic regression models were applied for association analyses. Among men, individual and group PA were associated with lower depressive symptoms compared with the no PA group among men [Individual: OR:0.59 (95%CI:0.40 to 0.86); Group: OR:0.42 (95%CI:0.29 to 0.59)]. Sensitivity analysis revealed that men involved in group PA were 40% [OR:0.60 (95%CI:0.38 to 0.94)] less likely to present elevated depressive symptoms when compared with individual PA. In females, no differences in depressive symptoms were observed comparing individual PA [OR:0.89 (95%CI:0.71 to 1.11)] and group PA [OR:0.86 (95%CI:0.54 to 1.37)] with the no PA group. Activities that are more likely to be a group PA demonstrated a stronger association with low depressive symptoms among men, but not women. Highlights: Both contexts of leisure-time physical activity are associated with reduced depressive symptoms, especially among men. Among men, activities that are more likely to be practiced in group are strongly associated with lower depressive symptoms. Interventions should focus on the increase of physical activity especially through group-based physical activity practice.